Misconceptions and lack of vaccine confidence: even First Responders are not spared. (13th November 2019) - Riccò, M; Vezzosi, L; Balzarini, F; Mezzoiuso, A G; Veronesi, L; Colucci, M E; Signorelli, C
Abstract: Introduction: First Responders (FR) are front-line healthcare workers potentially exposed to different infectious agents. Characterizing their knowledge, attitudes and practices (KAP) towards immunizations has therefore the potential to significantly improve occupational health and safety. Methods: A questionnaire-based cross-sectional study was performed during October 2018, collecting a convenience sample among FR from the Parma Province. Participants were inquired on 3 recommended vaccinations (i.e. seasonal influenza vaccine, SIV; measles vaccine, MeV; pertussis vaccine, Pa) and for meningococcal vaccines (MEN, not officially recommended in FR). Knowledge status (KS) and Risk Perception (RP) were assessed as percent values. Multivariate odds ratios (mOR) for factors associated with vaccination status were calculated by means of a binary logistic regression analysis. Results: A total of 161 questionnaires were retrieved (mean age 45.1±14.1 years; seniority 10.8 ± 8.6 years). Internal consistency was good (Cronbach's alpha = 0.894). KS was unsatisfying (46.5% ± 32.4) with uncertainties on the recommendations for MeV and MEN (39.1% and 34.2% incorrect answers). The majority of respondents were favorable towards MEN (89.4%), MeV (87.5%), Pa (83.0%), while 55.3% exhibited a favorable attitude for SIV, and 28.0% had received SIV 2018 (self-reported lifetime status for MEN 26.1%, MeV 42.2%, Pa 34.8%). RP was unsatisfying, particularly for SIV (33.9% ± 18.4). Interestingly enough, neither KS nor RP were associated with vaccination rates, being the main predictor for SIV 2018 a seniority ≥ 10 years (mOR 3.26, 95%CI 1.35-7.91), and higher educational achievements for both Pa (mOR 3.27, 95%CI 1.29-8.30) and MeV (mOR 2.69, 95%CI 1.09-6.65). Conclusions: Reasons for vaccination gaps in FR apparently do not find their roots only in FRs' incomplete KS or RP. However, the very low vaccination rates for SIV, MeV and Pa recommends stronger and more appropriate information campaigns. Key messages: Main drivers of vaccination status in First Responders are not solely their knowledge status or risk perception. Achieving better vaccination rates in First Responders requires the understanding of a complex interplay of individual factors.